Pleural effusions associated with pancreaticopleural fistula. Issue 8 (August 1993) - Williams, S G; Bhupalan, A; Zureikat, N; Thuluvath, P J; Santis, G; Theodorou, N; Westaby, D
Abstract : Two cases of pancreaticopleural fistula are reported. The delay in diagnosis and extensive investigations performed highlight the need for pleural fluid amylase estimation at an early stage.